2000 Solid-State, Actuators, and Microsystems Workshop Technical Digest 2000
DOI: 10.31438/trf.hh2000.2
|View full text |Cite
|
Sign up to set email alerts
|

A Flat High-Frequency Scanning Micromirror

Abstract: We present the Staggered Torsional Electrostatic Combdrive (STEC) fabrication process that creates thick mirrors with hightorque actuators, thereby allowing high-speed optical scanning with large angular deflections.We have demonstrated a 550 pmdiameter mirror capable of scanning an optical angle of 24.9" at its 34 kHz resonant frequency with less than 30 nm static and dynamic deformation.The optical resolution is 350 pixels -very near the diffraction-limited resolution of 355 pixels with 655 nm wavelength lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(26 citation statements)
references
References 7 publications
0
26
0
Order By: Relevance
“…In addition to the thicker substrate bulk micromachining allows for, mirror reinforcement structures and additional mechanical connections to the mirror frame can also substantially reduce the dynamic deformation. The earliest studies on well-characterized MEMS mirrors were published in 2000 by Urey et al [26] and Conant et al [43]. Common methods to measure dynamic deformation are monochromatic stroboscopic interferometry and stroboscopic white light interferometry [26], [44].…”
Section: B Dynamic Deformationmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to the thicker substrate bulk micromachining allows for, mirror reinforcement structures and additional mechanical connections to the mirror frame can also substantially reduce the dynamic deformation. The earliest studies on well-characterized MEMS mirrors were published in 2000 by Urey et al [26] and Conant et al [43]. Common methods to measure dynamic deformation are monochromatic stroboscopic interferometry and stroboscopic white light interferometry [26], [44].…”
Section: B Dynamic Deformationmentioning
confidence: 99%
“…The direct drive is easier to design and has a richer literature, but for each of the major actuation principles there are distinct advantages. ES scanners using a direct drive are performance limited by damping power losses and the small actuator capacitance due to limited available area when the fingers are to be directly connected to the mirror [43], [77]- [82]. Experimental evidence for significant reductions in air damping of ES when the comb finger gaps are increased Fig.…”
Section: Direct Drive Vs Indirect Drivementioning
confidence: 99%
See 2 more Smart Citations
“…Torsional microscanners typically require substantial torque and to produce this torque by electrostatic drivers, previous research [10] has shown the effectiveness of using vertically offset comb pairs for the drivers. Fabrication of these vertically offset combs has been a considerable challenge to earlier MEMS technologists, who have found the solutions using the following demanding procedures: 1) carrying through critical alignment steps in a two-wafer process [10], 2) controlling and replicating the properties of materials such as photoresist or bimorph layers so that these materials can function as hinges [11], 3) postprocess annealing in a high-temperature furnace following the hand assembly of lids on device chips [12], and 4) depositing multiple-masking layers (composed of silicon dioxide and silicon nitride) [13] to create the offset combs. We decided to focus our research on the development of fabrication methods that would produce vertically offset comb pairs using more conventional integrated-circuit (IC) processing tools.…”
mentioning
confidence: 99%